2018
DOI: 10.1186/s12883-018-1231-0
|View full text |Cite
|
Sign up to set email alerts
|

First three cases of scalp temperature change in symptomatic areas affected by nummular headache: a case report

Abstract: BackgroundNummular headache is a distinct headache disorder characterized by a rounded or elliptical symptomatic area that is typically 2 to 6 cm in diameter and does not change in shape or size with time. Although the pathomechanism is still not clear, nummular headache is thought to be a primary headache disorder. To date, more than 250 cases have been reported; the symptoms of this disease vary, but no cases with scalp temperature changes in the symptomatic areas have been reported yet. In this study, we pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…Conventional studies have reported that dryness of the skin, dandruff conditions, various medical histories, and heat sensation of the scalp are highly associated with scalp sensitivity . In Table , the proportion of dry scalp in the SS group was the highest.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…Conventional studies have reported that dryness of the skin, dandruff conditions, various medical histories, and heat sensation of the scalp are highly associated with scalp sensitivity . In Table , the proportion of dry scalp in the SS group was the highest.…”
Section: Resultsmentioning
confidence: 90%
“…High heat on the scalp can lead to various diseases, including hair loss, and is also known to have a negative impact on hair . In this study, the scalp temperature of 125 participants was measured in five areas: The frontal area, vertex area, occipital area, right temporal area, and left temporal area, using the contactless thermometer.…”
Section: Resultsmentioning
confidence: 99%
“…Case reports and case series have shown pain disappearance in 27/43 (40%) [5,[23][24][25][26][27][28] of NH patients treated with gabapentin. Improvement in the intensity of pain was found in 18/39 (46%) patients [5,25,29,30], while no response was reported in 5/6 (83%) patients [21,30,31] and lack of tolerability in 1 additional case [32]. These results could indeed be due to a publication bias, with positive studies more likely to report the clinical benefit; further, only two large series have been published in the literature so far [5,6].…”
Section: Discussionmentioning
confidence: 95%
“…The occipital location is also relatively frequent, with locations in the temporal or frontal regions or in the border territories being less common. Normally the pain affects one of the two sides of the head; however, more than 50 cases have been reported with the painful area over the midline (4,6,7,9,15,24,32,37,55,58,59,62,65). Thirty-six patients have also been reported with bifocal NH, with two separate areas of pain (22,23,30,32,34,38,58,60).…”
Section: Nummular Headachementioning
confidence: 99%
“…Overall, 10 cases with obvious trophic changes can be found in the literature (1,16,28,39,57), but careful palpation of the symptomatic area could probably detect subtle skin depression in a higher proportion of NH patients. Local changes in temperature (warm or cold) have also been reported in three patients with no other skin abnormalities (55). There is also a description of a child who started to present NH at the age of four years in an area of the scalp that had a lighter tuft of hair since birth (27).…”
Section: Nummular Headachementioning
confidence: 99%